Prospects for utilization of modern technologies for cattle improvement in Africa - Peters, S.O.; Ibeagha-Awemu, E.M.; Kwoji, I.D.; Mrode, Raphael A.; Ozoje, M.O.; Mbah, D.A.; Houaga, I.; Okpeku, M.; Fayemi, P.O.; Trocmé, D.; Opoola, O.; Adeleke, M.A. (Springer, 2025)
This chapter discusses the prospects of the utilization of modern technologies for cattle improvement in African livestock production systems. The first section gives a general overview of modern technologies and their application for improving cattle in the African continent. Section 22.1 discusses the general overview of how different molecular information improves the development of large ruminants in Africa. The section outlines some practical case studies where molecular information has been used for the detection of genomic variations in African cattle and buffalo, the use of genetic markers to assign individuals to breeds, and parentage identification. It concludes with the use of molecular information in gene editing and transgenic animals in animal production. In Sect. 22.3, the prospect for the application of modern technology in developing livestock feeds and feeding is discussed with practical examples. The subsequent sections discuss the application of modern technologies in improving livestock housing and husbandry systems (Sect. 22.4). Other modern technological advancements, including the development of diagnostic tests for detecting genetic defects using single nucleotide polymorphisms (SNPs), using genomic markers for selective breeding, and genome editing to improve productivity and control of deleterious alleles in livestock, are also discussed. The chapter also reviews the application of modern technologies to improve livestock health. In each case, practical examples are outlined as case studies where the technologies are applied in the African setting. The chapter concludes by looking at challenges and constraints in the implementation of modern technologies in cattle and buffalo production in Africa. Potential solutions are suggested.